The cost of segregation in social networks - Nizar Allouch (Fondazione Eni Enrico Mattei (FEEM), 2013)
This paper investigates the private provision of public goods in segregated societies. While most research agrees that segregation undermines public provision, the findings are mixed for private provision: social interactions, being strong within groups and limited across groups, may either increase or impede voluntary contributions. Moreover, although efficiency concerns generally provide a rationale for government intervention, surprisingly, little light is shed in the literature on the potential effectiveness of such intervention in a segregated society. This paper first develops an index based on social interactions, which, roughly speaking, measures the welfare impact of income redistribution in an arbitrary society. It then shows that the proposed index vanishes when applied to large segregated societies, which suggests an asymptotic neutrality of redistributive policies.
Keywords: C72; D31; H41; 330; Public Goods; Segregated Society; Private Provision; Networks; Bonacich Transfer Index